2020
DOI: 10.59331/jasd.v3i3.135
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Improved Upland Rice Production Practices Among Farmers in Balanga Local Government Area of Gombe State, Nigeria

Abstract: The study investigated acceptability of improved upland rice production practices among farmers in Balanga local government area of Gombe State, Nigeria. Multi stage sampling procedure was used to determine the sample of the study. Primary data were collected from 154 samples of rice farmers through the use of structured questionnaire. Descriptive statistics such as percentages, means and adoption index were used to achieve objectives of this study. The study revealed that farmers in the study area have an ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The crop has much potential to be grown throughout the year. Rice production is one of the major agricultural enterprises which provides employment, food, and income to a large proportion of farmers in Gombe State in particular and Nigeria in general (Bala and Mumini, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crop has much potential to be grown throughout the year. Rice production is one of the major agricultural enterprises which provides employment, food, and income to a large proportion of farmers in Gombe State in particular and Nigeria in general (Bala and Mumini, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A study was conducted to determine the Level of Adoption of NERICA1 Technologies among Farmers in Gombe State by Bala et al (2019). Another study was conducted by Bala and Mumini (2020) to examine the acceptance and use of Improved Upland Rice Production Practices in the Balanga Local Government Area of Gombe State. The results of these studies indicated a low level of adoption of technologies.…”
Section: Introductionmentioning
confidence: 99%